Metodologi Pengawasan dengan Pendekatan Agama dalam Dunia Pendidikan - Ismail , Miftahul Ulum (LPPPM STAI Darul Hikmah Bangkalan, 2020)
Supervision with a religious approach is supervision by a leader to subordinates through the empowerment of religious values to encourage self-supervision of civil servants to clean and free of deception. And to become a supervisor, one must have the qualification and competency standards as defined in Minister of Education Regulation No. 12 of 2007 concerning standard school inspections. In addition, the task of supervision also requires ethical or regulatory resources as a guide to maintain the dignity and quality of the school so that no party is harmed.